Modern Day Slavery: What Drives Human Trafficking in Europe? - Diego Hernandez; Alexandra Rudolph (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
At a time of increased attention on the international agenda for human trafficking, this paper examines the determinants of human trafficking inflows to 13 European countries based on official records. By employing a fixed effects zero-inflated, negative binomial gravity-type model, we address data characteristics appropriately. The econometric analysis suggests that human trafficking occurs in well established routes for migrants and refugees. Victims are more likely to be transported to, and exploited in, host countries with suboptimal institutional quality levels. Countries whose nationals do not require a visa for short term visits are especially prone to being potential source countries. Legal status and regulation of commercial sex services does not affect the pattern of trafficking flows.
Keywords: F22; J61; K14; K42; O17; 330; Human Trafficking; Gravity Model; Illegal Migration; International Organized Crime